2010
DOI: 10.1371/journal.pone.0010139
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Proteasome in Excitotoxicity-Induced Cleavage of Glutamic Acid Decarboxylase in Cultured Hippocampal Neurons

Abstract: Glutamic acid decarboxylase is responsible for synthesizing GABA, the major inhibitory neurotransmitter, and exists in two isoforms—GAD65 and GAD67. The enzyme is cleaved under excitotoxic conditions, but the mechanisms involved and the functional consequences are not fully elucidated. We found that excitotoxic stimulation of cultured hippocampal neurons with glutamate leads to a time-dependent cleavage of GAD65 and GAD67 in the N-terminal region of the proteins, and decrease the corresponding mRNAs. The cleav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 76 publications
(110 reference statements)
1
11
0
Order By: Relevance
“…Recent reports suggest that cleavage of fGAD65 occurs under glutamate alterations that contribute to sustained calpain activation [30][31]. In this study, we have concluded that cleavage of fGAD65 reduced GABA neurotransmission, which is a pathological outcome of the cleavage mechanism.…”
Section: Discussionsupporting
confidence: 51%
“…Recent reports suggest that cleavage of fGAD65 occurs under glutamate alterations that contribute to sustained calpain activation [30][31]. In this study, we have concluded that cleavage of fGAD65 reduced GABA neurotransmission, which is a pathological outcome of the cleavage mechanism.…”
Section: Discussionsupporting
confidence: 51%
“…However, an effective strategy should also prevent the calpain-mediated cleavage of the vesicular GABA transporters, which affects their delivery to the synapse by removing a targeting sequence [23,49]. Cleavage of glutamic acid decarboxylase, the enzyme that mediates the rate limiting step in the synthesis of GABA from glutamate, also decreases the synthesis of the neurotransmitter [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…internalization; iii) the same mutation reduced significantly OGDinduced cell death. The neuroprotection provided by the phosphomimetic mutant of GABA A R β3 subunit, resulting from receptor activation by endogenous GABA, is highly remarkable considering that less than 10% of the cells present in the culture are GABAergic (Baptista et al, 2010). The triple arginine motif of the β3 GABA A R subunit that mediates direct binding of the receptor to the clathrin adaptor protein AP2 plays a key role in regulating the surface distribution of the receptor (Smith et al, 2012).…”
Section: Discussionmentioning
confidence: 99%